2008
DOI: 10.1074/jbc.m804065200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Viral NS3-4A Protease Activity Is Enhanced by the NS3 Helicase

Abstract: Non-structural protein 3 (NS3) is a multifunctional enzyme possessing serine protease, NTPase, and RNA unwinding activities that are required for hepatitis C viral (HCV) replication. HCV non-structural protein 4A (NS4A) binds to the N-terminal NS3 protease domain to stimulate NS3 serine protease activity. In addition, the NS3 protease domain enhances the RNA binding, ATPase, and RNA unwinding activities of the C-terminal NS3 helicase domain (NS3hel). To determine whether NS3hel enhances the NS3 serine protease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
93
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 38 publications
3
93
1
1
Order By: Relevance
“…The data presented in this work expand the known functions of HCV NS3 helicase. It has been shown previously that the activity of HCV NS3 helicase domain is modulated by other factors such as the protease domain of HCV NS3 [2] and HCV NS5B [5]. Although it is outside the scope of this article, in the future it would be of interest to see how these factors affect the activities described in this work.…”
Section: Resultsmentioning
confidence: 87%
“…The data presented in this work expand the known functions of HCV NS3 helicase. It has been shown previously that the activity of HCV NS3 helicase domain is modulated by other factors such as the protease domain of HCV NS3 [2] and HCV NS5B [5]. Although it is outside the scope of this article, in the future it would be of interest to see how these factors affect the activities described in this work.…”
Section: Resultsmentioning
confidence: 87%
“…The isolated domains of NS3, i.e., the protease and helicase domains are functional on their own. It has been reported that in the full-length enzyme the NS3/4A protease enhances RNA binding and unwinding by the helicase and that also the helicase enhances protease activity (7,8). In the past decade, HCV NS3/4A protease has emerged as an important drug target for treatment of HCV infection.…”
mentioning
confidence: 99%
“…Each of the two domains can be expressed separately and retain activity (18). However, the activities are interdependent, since recently it was shown that the NS3 helicase domain stimulates the serine protease activity (19). Both protease and helicase activities are required for viral replication (20).…”
mentioning
confidence: 99%